Study on the properties of MgO-Fe-C bricks as the linings of vanadium-extraction converters - LIU Lei; SUN Wen-jie; ZHANG Ling-xi; LI Xue-hui (工程科学学报, 2016)
To extend the service life of MgO-C bricks which used as the linings of vanadium-extraction converters, MgO-Fe-C bricks were fabricated in this study. The service properties of this novel refractory were comparatively investigated between traditional MgO-C bricks and MgO-Fe-C bricks. The results show that the poor sinterability and anti-erosion property of the decarburized layer at the service temperature of 1400 ℃ are responsible for the short service life of MgO-C bricks. However, for MgO-Fe-C bricks, Fe particles are oxidized in the oxidized layer and in-situ MgO-FeOss forms under the working condition. This can effectively improve the sintering performance, form a decarburized layer with enhanced compactness and bonding strength, and significantly improve the oxidation resistance and slag corrosion resistance of this layer, contributing to extend the service life. MgO-Fe-C bricks have a promising prospect of applications in the substitute for MgO-C bricks as the linings of vanadium-extraction converters.